The administration of a Nigerian university - Taiwo, C. O. (Ikeja, Lagos : Nelson Publishers, 1995)
This book is on the working of the governing council of a Nigerian university, which is the responsible body for the broad policy and administration of the university.
Includes index.
Includes bibliographical references (p. 207).
osa 28/09/2016
Loans
Keywords: Universities and colleges; Administration of education; Universities; University administration $1 (BNigeria.s; Educational administrators $1 (BNigeria $1 (BBiographies.s; Universities and colleges -- Nigeria